FAKTOR-FAKTOR YANG MEMPENGARUHI KEGAGALAN PEMBERIAN ASI EKSKLUSIF WILAYAH KERJA RW 06 KEL.PONDOK PUCUNG KEC. KARANG TENGAH TANGGERANG KOTA PERIODE OKTOBER –DESEMBER TAHUN 2022 - Sumarmi Sumarmi (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
The proportion of breastfeeding in the group of infants aged 0 months 73.1%, 1 month 55.5%, 2 months 43%, 3 months 36% 6 months 16.7%. With increasing age of the baby there is a pattern of decreasing breastfeeding by 1.3 times or by 77.2%. The research design uses descriptive analytic research with a cross sectional approach. The population of this study were all babies aged 7 months and over (98 babies) in the working area of ​​Kel. Karang Tengah Kec. Ciledug Tangerang City in 2012. Sampling technique using accidental sampling. The results of statistical tests obtained p = 0.059 (p = < 0.05) so it can be concluded that there is no significant relationship between maternal age and failure of exclusive breastfeeding. p = 0.036 (P <0.05), there is a significant relationship between elementary and junior high school mothers' education and failure of exclusive breastfeeding. The value of p = 0.569 (p => 0.05), there is no significant relationship between working mothers and non-working mothers with failure of exclusive breastfeeding. Value of p=0.000 (P<0.05), there is a significant relationship between poor mother's knowledge and failure of exclusive breastfeeding It is expected that pregnant women and nursing mothers, their husbands and their families will always provide explanations about the importance and benefits of 6 months of exclusive breastfeeding and its management starting from pregnancy, when the baby is born, until the age of 6 months.